Analysis Of Electronic Word Of Mouth As An Intervening Variable Between Store Atmosphere And Purchase Decisions (Survey Of Consumers Cendana Coffee, Food & Beverage Tasikmalaya) - Hernawati, Dina; Fitriadi, Budhi Wahyu; Ghonisyah, Ghaling Achmad Abdul (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the influence of Electronic Word Of Mouth as an intervening variable between Store Atmosphere and Purchasing Decisions on Cendana Coffee, Food & Beverage Tasikmalaya consumers. The development of the food and beverage industry in Tasikmalaya encourages relationships between small and large food and beverage businesses, especially in the café industry. When consumers experience a positive atmosphere in a coffee shop, they are more likely to share their positive experiences online. This has the potential to influence purchasing decisions. The research method used is quantitative with a causal associative research type with a survey approach. Data were collected through an online questionnaire distributed to 100 consumer respondents of Cendana Coffee, Food & Beverage Tasikmalaya, selected using a purposive sampling technique. Data analysis was carried out using validity tests, reliability tests, and simple mediation models with the help of SPSS software version 25. The results of the study show that store atmosphere has a significant influence on purchasing decisions of Cendana Coffee Food & Beverage Tasikmalaya consumers. Store Atmosphere has a significant influence on Electronic Word Of Mouth at Cendana Coffee Food & Beverage Tasikmalaya. Store Atmosphere has a significant influence on purchasing decisions through Electronic Word Of Mouth. Electronic Word Of Mouth is proven to be able to mediate Store Atmosphere on purchasing decisions at Cendana Coffee Food & Beverage Tasikmalaya.